Sisters of Belfast a Novel - Maure, Melanie (New York Harper, 2024)
"Orphaned during the Second World War, Aelish and Isabel McGuire--known as the twins of Belfast--are given over to the austere care of the Sisters of Bethlehem. Though they are each all the other has, the girls are propelled in opposite directions as they grow up. Rebellious Isabel turns her back on the church and Ireland, traveling to Newfoundland where she pursues a perilous yet independent life. Devout Aelish chooses to remain in Northern Ireland and takes the veil, burying painful truths beneath years of silence. For decades the two are separated, each unaware of the other's life. But after years of isolation Aelish is unexpectedly summoned to Newfoundland, where she and her estranged sister begin to bridge the chasm between them. Reunion brings to light the painful secrets and seismic deceptions that have kept these sisters apart, leaving the McGuire twins to begin reconstructing their understanding about themselves as women and as family--what they know of love, hope, and above all, forgiveness."--
113326
Keywords: Sisters; Twins; Orphans; Nuns; Estranged families; Family secrets; Self-realization in women; Belfast (Northern Ireland) -- Fiction; Newfoundland and Labrador -- Fiction; Northern Ireland -- Fiction; Historical fiction